Learning Video Using a Culturally Responsive Teaching Approach in the IPAS Subject to Improve Students’ Learning Outcomes - Kadek Yulia Kusumayani; I Gusti Ayu Tri Agustiana; Made Vina Arie Paramita (Universitas Pendidikan Ganesha, 2025)
Learning outcomes in elementary school IPAS remain low due to less contextualized instruction and limited media that accommodate students’ cultural backgrounds. This study aimed to develop and evaluate video-based learning media using a Culturally Responsive Teaching (CRT) approach to enhance students’ learning outcomes and engagement in IPAS. The study employed a developmental research design using the ADDIE model, involving content experts, media experts, teachers, and students as subjects in individual, small group, and class-level trials. Data were collected through interviews, questionnaires, and tests, and analyzed using a combination of qualitative, quantitative, and inferential statistical methods. The results showed that the video media were developed contextually, adapted to students’ local culture. Validity indices from content and media experts were 0.94 and 0.98, respectively, indicating very high validity. The media were highly practical, with a 99% feasibility rating from teachers and students, and proved effective, as evidenced by a significant increase in learning outcomes based on t-test results. The study concludes that CRT-based video media are valid, practical, and effective in enhancing conceptual understanding, active engagement, and positive attitudes toward students’ own culture. The findings highlight the importance of integrating cultural context into learning media development to create meaningful, student-centered learning experiences.